Effect of high pressure treatment applied on starter culture or on semi-ripened cheese in the quality and ripening of cheese in brine. (December 2016) - Giannoglou, Marianna; Karra, Zoi; Platakou, Eleni; Katsaros, George; Moatsou, Golfo; Taoukis, Petros
Abstract: Cheese ripening acceleration is of continuous interest for the industry. High-pressure (HP) treatment of starter cultures used in cheese-manufacturing offers the potential to accelerate ripening by increasing the activity of their intracellular peptidases that contribute in the development of desired cheese organoleptic characteristics. The objective of the present research was the investigation of the effect of HP treatment (200 MPa-20 °C - 20 min) directly on white brined cheese or on the starter culture used for its manufacture ( Str. thermophilus:L. lactis : L. bugaricus 2:1:1 ). For this purpose, the microbial, textural, physicochemical and organoleptic characteristics and proteolysis were assessed during the 2nd stage of ripening in cold stores. Control cheese without any treatment was also studied. Cheeses made with HP-treated starters had increased secondary proteolysis. Organoleptic scoring of these cheeses was higher during the whole storage period compared to control and HP-treated cheese. Their superiority was evident even at the early stages of ripening in cold stores, since no bitterness was detected. On the contrary, although HP treated cheeses showed the highest increase in aminopeptidases activities, this was not correlated with the studied ripening indices or the organoleptic characteristics. According to the results, HP-treated starter culture can accelerate proteolysis and potentially the ripening of cheese-in-brine. Industrial relevance: The data obtained from this work suggest that application of HP treatment under optimized conditions on cheeses in brine starter cultures or on whole cheeses can be effectively used for the production of products with reduced ripening time. This is of great importance for the cheese industries, since the storage period for ripening is long (higher than two months), while applying HP treatment as suggested in this study, this time may be reduced to less than one month, producing cheeses of superior quality. Highlights: Mature cheese characteristics were obtained earlier using HP-treated starter cultures. Cheeses made with HP treated starters presented superior organoleptic characteristics. HP treated starters during cheese manufacturing increases secondary proteolysis. HP-treated starter culture can accelerate proteolysis and shorten ripening time.